2020
DOI: 10.1016/j.isci.2020.101621
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Bioprinter Specifically Designed for the High-Throughput Production of Matrix-Embedded Multicellular Spheroids

Abstract: HIGHLIGHTS3D bioprinter for the highthroughput production of embedded 3D multicellular spheroids Bioprinted spheroids are biologically similar to manually produced spheroids Parameters such as spheroid size and embedding affect the response toward doxorubicin High-throughput screening applications with high content imaging and viability assay

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 36 publications
1
59
0
Order By: Relevance
“…In this process, a hydrogel bio-ink is deposited layer-by-layer and cell droplets are placed in the center of the hydrogel cup. Over time, the cells aggregate into spheroids 53 . The precise spheroid fabrication capacity of 3D printing has greatly aided spheroid research.…”
Section: Spheroid Fabrication Methodsmentioning
confidence: 99%
“…In this process, a hydrogel bio-ink is deposited layer-by-layer and cell droplets are placed in the center of the hydrogel cup. Over time, the cells aggregate into spheroids 53 . The precise spheroid fabrication capacity of 3D printing has greatly aided spheroid research.…”
Section: Spheroid Fabrication Methodsmentioning
confidence: 99%
“…Briefly, the authors proposed a bespoke drop-on-demand 3D bioprinter able to print a high density of cells in a single droplet directly into a hydrogel mold using a solenoid microvalve printhead. An alginate cup was firstly printed in a 96-well plate and then a cell-laden ink with 250 million cell/mL printed into the cup; inside the matrix, a combination of gravitational forces and ECM secretion by cells caused the formation of single embedded spheroid for each well in 24 h. Interestingly, as the cup was filled by the growing spheroid, the latter conformed to the shape of the cup confirming the bioprinter ability to controlled shape by matching cup size, cell volume and density in each droplet together with relevant tumor-like properties [ 44 ].…”
Section: Multicellular Spheroidsmentioning
confidence: 99%
“…Alternately, hydrogels as spheroids-embedding molds can help to control their size, rate of growth, drug responses and creating a more realistic model of in vivo situation [ 43 ]. For example, Utama et al [ 44 ] established a custom high-throughput bioprinting method for producing alginate and calcium chloride hydrogel-embedded spheroids of three different tumor cell lines (neuroblastoma, non-small cell lung cancer and glioblastoma cells) with controlled spatial distribution and size obtaining statistically reliable data in comparison to others research works. Briefly, the authors proposed a bespoke drop-on-demand 3D bioprinter able to print a high density of cells in a single droplet directly into a hydrogel mold using a solenoid microvalve printhead.…”
Section: Multicellular Spheroidsmentioning
confidence: 99%
“…In a very interesting study of R. Utama et al, the formation of matrix-embedded multicellular spheroids prepared in high-throughput (HTP) was described [ 96 ]. Authors developed an enabling technology consisting of a bespoke drop-on-demand 3D bioprinter capable of HTP printing of 96-well plates of spheroids.…”
Section: 3d Bioprintingmentioning
confidence: 99%
“…Additionally, the opportunity of HTP drug screening was investigated on neuroblastoma spheroids, exposed to doxorubicin. It was shown that sensitivity to spheroid size, embedding and how spheroids conform to the embedding affect the response toward doxorubicin [ 96 ].…”
Section: 3d Bioprintingmentioning
confidence: 99%